STRATEGI PEMASARAN PENGRAJIN TAHU DAN TEMPE AKIBAT KENAIKAN HARGA BAHAN BAKU TAHUN 2022 - Meyer Nixon Dewantara Nainggolan; Gazali Amin; Suriadi Suriadi (Paser Institute Management and Busines, 2024)
Tofu and tempeh are processed foods with fairly high nutritional value and are made from soybeans. Soybeans are a versatile plant that is highly beneficial in terms of food and nutrition. The price of soybeans increased in 2022. One of the factors influencing this increase is the COVID-19 pandemic, which has been a reason for the rise in soybean prices, the raw material for tofu and tempeh. This increase occurred from the beginning of 2022 until the end of the year. The reduced availability of raw materials due to the rise in soybean prices also impacted small and medium-sized tofu and tempeh businesses in the city of Bontang. Therefore, the author conducted an interview with one of the tofu and tempeh artisans in Bontang. The results of the interview with one of the business owners indicated that the rise in soybean prices significantly affected their sales and production, making it difficult to sustain their business. Various efforts have been made by tofu and tempeh artisans to meet market demands, such as reducing the size of tofu and tempeh but still using imported soybeans to maintain the taste and shelf life of the products. Therefore, this scientific work aims to analyze the impact of soybean price increases on tofu and tempeh artisans using qualitative research and SWOT analysis to determine the marketing strategies that business owners should implement to sustain their businesses.